Penerapan Algoritma Colussi Dalam Mencari Data Aki Di Toko “Dunia Aki” Berbasis Web - Rozali Toyib; Muntahanah Muntahanah; Marhalim Marhalim; Aliman Dani (Jurnal Media Infotama, 2024)
Sales information system provides information to manage the sale of products/services generated by the store. Sales service becomes crucial as competition between stores intensifies. Therefore, the development of sales information systems to facilitate consumer service continues to evolve. The development of web-based sales information systems provides convenience for stores in continuous online sales service. Web media also serves as a means for the store to achieve strategic goals. The advantage of web media lies in its broad and extensive reach. Additionally, the information presented can be detailed and up-to-date. Process analysis is based on a review of the sales system used by the store, utilizing the Colussi algorithm and depicted through IDEF, ERD, and URLs to illustrate the relationships between entities in the sales information system. The physical design of this sales information system is outlined using PHP programming language and MYSQL database. Based on the input-output design, this study provides an overview of a web-based sales information system capable of meeting store requirements